THE EFFECT OF RELIABILITY, RESPONSIVENESS, ASSURANCE, EMPATHY, AND TANGIBLES TO SALES INCREASE AT PT. J.CO DONUTS & COFFEE MANADO - Maukar, Filadel Jesse; Kawet, Lotje; Dotulong, Lucky O.H (FEB Universitas Sam Ratulangi Manado, 2015)
The current businesses are faced with a growing number of companies engaged in the field of food and beverage, so the competition becomes tight. Good service quality will surely make consumers happy and feel comfortable while shopping. This study aims to determine the effect of reliability, responsiviness, assurance, empathy, and tangibles of company towards the sales increase PT J.CO Donuts & Coffee Manado Town Square, both simultaneously or partially. This study uses quantitative methods. The number of respondents is 100 people which were selected using accidental sampling. the research method used is the associative method using the multiple linear regression analysis technique. Simultaneous testing provides results of the five variables which are reliability, responsiveness, assurance, empathy, and tangibles to significantly effect the sales increase. Partially the four variables which are reliability, responsiveness, assurance, and tangibles effected significantly, and empathy has no effect, because it is not the main concern of consumers when doing a transaction The management of PT. J.CO. Donuts & Coffee should improve the reliability, responsiveness, assurance, and tangibles so corporate profits will increase. Keywords: reliability, responsiveness, assurance, empathy, tangibles, sales increase.